Circular Economy Development Policy in Magetan Regency: Case Study of the Leather Industry and its Impact on Improving the Community's Economy: Kebijakan Pengembangan Ekonomi Sirkuler di Kabupaten Magetan: Studi Kasus Industri Kulit dan Dampaknya terhadap Peningkatan Ekonomi Masyarakat - Sukarsono, Faza Muhammad; Gamaputra, Gading; Winata, Muhammad Danu; Kurniawan, Badrudin; Noviyanti; Lestari, Yuni; Wibisono, Haryo Kunto (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to analyze the circular economy development policy in Magetan Regency, focusing on the leather industry and its impact on improving the community's economy, especially on Jalan Sawo, Selosari Village. The method used is a qualitative approach, which includes in-depth interviews with industry players, direct observation at the location, and analysis of documents related to the policy. The results of the study indicate that the implementation of the circular economy policy not only increases community income through the creation of new jobs but also contributes to waste reduction and increased environmental awareness among the community. In addition, this study identifies challenges faced in implementing the policy, such as lack of training and technical support. Recommendations are provided to improve the effectiveness of this policy, including the need for collaboration between the government, private sector, and the community in creating a sustainable circular economy ecosystem. This research is expected to contribute to the development of better policies in the future.